2017
DOI: 10.1038/jp.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis in rural India: timing, microbiology and antibiotic resistance in a population-based prospective study in the community setting

Abstract: ObjectiveTo examine the timing and microbiology of neonatal sepsis in a population-based surveillance in the Indian community setting.Study DesignAll live born infants in 223 villages of Odisha state were followed at home for 60 days. Suspect sepsis cases were referred to study hospitals for further evaluation including blood culture.ResultsOf 12,622 births, 842 were admitted with suspected sepsis of whom 95% were 4–60 days old. Culture confirmed incidence of sepsis was 6.7/1000 births with 51% Gram negatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…The antibiogram of Klebsiella spp in Pinaki et al, were sensitive to amikacin (84%), gentamicin (86%), ciprofloxacin (73%), imipenem (100%), and cephalosporin (56%). 4 In South India study majority of the Klebsiella pneumonia isolates were resistant to all the antibiotics except amikacin and meropenem and 32% of them were ESBL producers. 6 In Delhi cohort study the prevalence of carbapenem resisstance among Klebsiella spp, Acinetobacter spp, were 38% and 78% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibiogram of Klebsiella spp in Pinaki et al, were sensitive to amikacin (84%), gentamicin (86%), ciprofloxacin (73%), imipenem (100%), and cephalosporin (56%). 4 In South India study majority of the Klebsiella pneumonia isolates were resistant to all the antibiotics except amikacin and meropenem and 32% of them were ESBL producers. 6 In Delhi cohort study the prevalence of carbapenem resisstance among Klebsiella spp, Acinetobacter spp, were 38% and 78% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar pattern of bacteriological profile i.e.69% gram negative organisms and 26% gram positives bacteria were found in Pinaki et al which was conducted on microbiological pattern in rural India and the most common organism were Klebsiella sp, followed by Staph aureus. 4 In Delhi cohort study conducted in multiple tertiary care centres, 64% isolates were gramnegative including Acinetobacter (22%), Klebsiella (17%), and Escherichia coli (14%). 5 Study conducted in South India tertiary care hospital by Bambala et al, found that Klebsiella pneumoniae was isolated from 66% of culture positive cases followed by Coagulasenegative staphylococci in 12% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…10 , 11 , 12 A study in India showed 10% positivity by blood culture, with organisms being predominantly Gram-negative (69%). 13 A study in Bangladesh examined 62 respiratory samples and found a high burden of viral infections (48%). 14 …”
Section: Introductionmentioning
confidence: 99%
“…CRP has been used to monitor response to infection and to assist in ruling out an infection. Most of these studies have been done in children, term, or near-term neonates using the lower CRP level cutoffs of <8 mg/dL or <10 mg/dL [35]. What does the study add to the existing knowledge?…”
Section: Resultsmentioning
confidence: 99%